A comparison study of clinician‐rated atopic dermatitis outcome measures for intermediate‐ to dark‐skinned patients. (1st April 2017) - Zhao, C.Y.; Hao, E.Y.; Oh, D.D.; Daniel, B.S.; Martin, L.K.; Su, J.C.; Rodrigues, M.; Murrell, D.F.
Summary: Background: Atopic dermatitis (AD) assessment is more difficult in patients with skin of colour (SOC). Objectives: To compare the reliability of commonly used outcome measures for assessing AD in patients with SOC and to evaluate a novel greyscale in this population. Methods: Twenty‐five patients with AD each attended a 1‐day scoring exercise based in either Sydney or Melbourne, Australia. Each patient was scored by the same five physicians using the Eczema Area and Severity Index (EASI), objective Scoring Atopic Dermatitis (oSCORAD), Investigator's Global Assessment (IGA) and a novel greyscale. Patients also completed the Patient‐Oriented Eczema Measure and quality‐of‐life measures. A Mexameter was used to measure baseline melanin indices. Ten random patients were rescored to test intrarater reliability. Results: We included 11 light‐skinned patients (melanin index ≤ 200) and 14 patients with SOC (melanin index > 200) in the cohort. The inter‐rater intraclass correlation coefficients (ICCs) were EASI 0·83 [95% confidence interval (CI) 0·66–0·94] for light skin and 0·77 (95% CI 0·60–0·91) for SOC; oSCORAD 0·68 (95% CI 0·44–0·88) for light skin and 0·74 (95% CI 0·54–0·89) for SOC; and IGA 0·80 (95% CI 0·62–0·93) for light skin and 0·70 (95% CI 0·49–0·87) for SOC. The greyscale had an ICC of 0·78 (95% CI 0·60–0·91) when replacing the EASI's erythema scale for patients with SOC. All scores showed excellent intrarater reliability for all skin types. Erythema component analysis showed that erythema did not contribute to variability. Conclusions: EASI showed excellent reliability for patients of all skin colours, and is recommended as the optimal core measure for patients with all skin colours.